BinSPreader: Refine binning results for fuller MAG reconstruction - Ivan Tolstoganov; Yuri Kamenev; Roman Kruglikov; Sofia Ochkalova; Anton Korobeynikov (iScience, 2022)
Summary: Despite the recent advances in high-throughput sequencing, metagenome analysis of microbial populations still remains a challenge. In particular, the metagenome-assembled genomes (MAGs) are often fragmented due to interspecies repeats, uneven coverage, and varying strain abundance. MAGs are constructed via a binning process that uses features of input data in order to cluster long contigs presumably belonging to the same species.In this work, we present BinSPreader—a binning refiner tool that exploits the assembly graph topology and other connectivity information to refine binning, correct binning errors, and propagate binning to shorter contigs. We show that BinSPreader could increase the completeness of the bins without sacrificing the purity and could predict contigs belonging to several MAGs.BinSPreader is effective in binning shorter contigs that often contain important conservative sequences that might be of great interest to researchers.